Managing employees' performance in the Malaysian public sector: a critical analysis from organizational justice perspectives - Jamaiudin, Norhaslinda (Partridge, 2018)
This chapter explores issues surrounding the implementation of performance management framework, specifically Performance Management System (PMS)in Malaysian public sector from organizational justice perspective. As emphasized by the author, while there is a need to assess work performance in view of the continuous change and development in work industry, the system is hampered with poor execution and flaws. This in turn call for a thorough assessment and further improvement in order to ensure fair appraisal and work integrity among those involved in the industry